Prehospital Intervals and In-Hospital Trauma Mortality: A Retrospective Study from a Level I Trauma Center - Hassan Al-Thani (440106) (2023)
Background The increase in mortality and total prehospital time (TPT) seen in Qatar appear to be realistic. However, existing reports on the influence of TPT on mortality in trauma patients are conflicting. This study aimed to explore the impact of prehospital time on the in-hospital outcomes. Methods A retrospective analysis of data on patients transferred alive by Emergency Medical Services (EMS) and admitted to Hamad Trauma Center (HTC) of Hamad General Hospital (HGH; Doha, Qatar) from June 2017 through May 2018 was conducted. This study was centered on the National Trauma Registry database. Patients were categorized based on the trauma triage activation and prehospital intervals, and comparative analysis was performed. Results A total of 1,455 patients were included, of which nearly one-quarter of patients required urgent and life-saving care at a trauma center (T1 activations). The overall TPT was 70 minutes and the on-scene time (OST) was 24 minutes. When compared to T2 activations, T1 patients were more likely to have been involved in road traffic injuries (RTIs); experienced head and chest injuries; presented with higher Injury Severity Score (ISS: median = 22); and had prolonged OST (27 minutes) and reduced TPT (65 minutes; P = .001). Prolonged OST was found to be associated with higher mortality in T1 patients, whereas TPT was not associated. Conclusions In-hospital mortality was independent of TPT but associated with longer OST in severely injured patients. The survival benefit may extend beyond the golden hour and may depend on the injury characteristics, prehospital, and in-hospital settings. Other information Published in: Prehospital and Disaster Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1017/S1049023X20000904